STRATEGI KOMUNIKASI PEMASARAN TERPADU THE KAYON JUNGLE RESORT DALAM MENINGKATKAN BRAND AWARENESS - Aristia Dewi, Putu Ratih; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
The Kayon Jungle Resort is a five-star resort located in Payangan District, Gianyar Regency, Bali which has the tagline "Trully Ubud Escape" with the brand image as "The Best Honeymoon Resort". The purpose of this research is to determine the integrated marketing communication strategy used by The Kayon Jungle Resort in increasing brand awareness. This research uses a descriptive qualitative approach with a post-positivism paradigm. This study used purposive sampling and snowball sampling techniques to determining the informants. Data collected by observation, in-depth interviews and documentation. The results of this research indicate the marketing communication strategy used by The Kayon Jungle Resort in increasing brand awareness by applying the concept of a marketing mix with 4 elements, namely: product, place, price, promotion and promotional mix which consists of of 8 elements, such as advertising, sales promotion, personal selling, direct marketing, interactive marketing, public relations and events.   Keyword: Integrated Marketing Communication Strategy, Brand Awareness, The Kayon Jungle Resort, Marketing Mix, Promotional Mix